(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In the article, the psychological-pedagogical foundations of professional training of future visual arts teachers are highlighted, the methods of implementing integrative relations between them based on the use of active teaching methods are considered.